2022
DOI: 10.1111/vec.13231
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of airway pressure release ventilation in the management of respiratory failure and refractory hypercapnia in a dog

Abstract: Objective: To describe the use of airway pressure release ventilation (APRV) to relieve hypercapnia in a dog undergoing mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Además, un manejo inadecuado de oxígeno puede comprometer la cicatrización de las heridas postquirúrgicas, la oxigenación adecuada es esencial para la proliferación celular, la síntesis de colágeno y la angiogénesis, todos procesos cruciales para una cicatrización óptima (Capó et al, 2023), la falta de oxigenación puede retrasar la cicatrización, aumentar el riesgo de infección y complicar la recuperación del paciente (Kovak et al, 2022).…”
Section: Manejo De Oxígeno Inadecuado En El Paciente Quirúrgicounclassified
“…Además, un manejo inadecuado de oxígeno puede comprometer la cicatrización de las heridas postquirúrgicas, la oxigenación adecuada es esencial para la proliferación celular, la síntesis de colágeno y la angiogénesis, todos procesos cruciales para una cicatrización óptima (Capó et al, 2023), la falta de oxigenación puede retrasar la cicatrización, aumentar el riesgo de infección y complicar la recuperación del paciente (Kovak et al, 2022).…”
Section: Manejo De Oxígeno Inadecuado En El Paciente Quirúrgicounclassified
“…Information on the use of APRV in animals has been obtained primarily in experimental settings ( 101 ). However, two case reports in veterinary medicine suggest that this strategy is applicable for the management of hypoxemia due to aspiration pneumonia and refractory hypercapnia secondary to noncardiogenic pulmonary edema ( 106 , 107 ). While the first patient was switched to APRV after several days of conventional mechanical ventilation, the second patient was settled after a few hours of initiation of mechanical ventilation.…”
Section: Adjunct Therapies and Alternative Ventilatory Modesmentioning
confidence: 99%
“…In addition, increased need for sedatives, paralytics, and vasopressors was associated with its use ( 108 110 ). Safety profiles have even shown that high frequency oscillatory ventilation was associated with a trend toward increased risk of barotrauma and unfavorable hemodynamics ( 107 ). Therefore, guidelines in humans state that high frequency oscillatory ventilation should not be a routine practice in adults or pediatrics with hypoxemic respiratory failure ( 15 , 108 , 111 ).…”
Section: Adjunct Therapies and Alternative Ventilatory Modesmentioning
confidence: 99%
“…Little is known in veterinary medicine regarding the utility and most appropriate way to implement these rescue therapies. Two case reports highlight the successful use of APRV for the management of hypoxemia due to aspiration pneumonia and refractory hypercapnia secondary to non-cardiogenic pulmonary edema ( 8 , 9 ).…”
mentioning
confidence: 99%